Legal Consequences of Marriage During Iddah Period Based on Compilation Islamic Law - Sinta Pomahiya; Nur M. Kasim; Dolot Alhasni Bakung (Universitas Negeri Gorontalo, 2022)
Abstract: This journal discusses marriage during the Iddah period. In Article 2 of the Compilation of Islamic Law, it is stated that marriage according to Islamic law is marriage, which is a very strong mistaken gholiidhan contract to obey Allah's commands. However, not all Islamic teachings can be implemented properly. This is evidenced by the existence of couples who do not care about iddah issues. Carrying out iddah for women is considered a form of worship. The type of research used types of sociological research, which aims-describes the implementation of marriage during the Iddah period and the legal consequences of marriage during the Iddah period. The results of the study’s three main points can be concluded. First, the implementation of marriage during the iddah period is the same as marriage in general, it's just that the marriage is carried out during the iddah period so the marriage is invalid. Second, because the marriage law during the iddah period will arise, the husband and wife will not get a marriage certificate, and when the marriage takes place there will be hereditary problems. Keywords: Marriage; Iddah; Islamic Law Compilation